Breast MRI of ductal carcinoma in situ - Francescutti, Giuliana E. (Radiology and oncology (Ljubljana), 2002)
Background. The purpose of this study is to report our personal experience of 22 cases of ductal carcinoma in situ (DCIS) studied with magnetic resonance imaging (MRI). Patients and methods. From September 1995 to December 2001, 22 women diagnosed with DCIS lesions underwent contrast enhanced MRI within 7 days after mammographic examination. Dynamic MRI was performed with a 1 T system, using a three dimensional fast low angle shot (FLASH) pulse sequence before and after contrast media administration. We evaluated the morphologic features of the enhancement, the enhancement rate and the signal time intensity curve. Pathology was obtained in all cases. Results. The results of histopatological examination included: 15 DCIS and 7 DCIS with associated mi- croinvasive component or microfoci of invasive ductal carcinoma (IDC). On MRl,21 of 22 (95%) DCIS lesions showed contrast enhancement. Fourteen out of 15 pure DCIS lesions demonstrated respectively a low (3), undeterminate (5), and strong (6) enhancement. Morphologically, the enhancing lesion was focal in7, segmental in 4, and with linear branching in 3 cases. Wash out was found in 4 cases, plateau curve in 8 and Type 1 curve in 2 cases. Multifocality was present in 5 cases. All DCIS with associated microinvasion demonstrated contrast enhancement: 1/7 cases showed a low en- hancement, 2/7 showed an indeterminate enhancement and 4/7 showed a strong enhancement. Morphologically, the enhancing lesion was focal in 3/9, segmental in 5 and with linear branching in 1 case. The wash out was demonstrated in 3/7 cases, plateau curve in 3 and Type 1 curve in lcase. Multifocality was present in 3 cases. Conclusions. In conclusion, the sensitivity of MRI for DCIS detection is lower than that achieved for in- vasive breast cancer, however, contrast-enhanced MRI can depict foci of DCIS that are maminographically occult. (Abstract truncated at 2000 characters).
Keywords: breast; Breast Neoplasms; Carcinoma In Situ; Carcinoma, Intraductal, Noninfiltrating; Diagnosis; diagnostika; Dojka, novotvorbe; dojke; karcinom; Karcinom in situ; Karcinom intraduktalni, neinfiltracijski; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Mammography; Mamografija; radiološka diagnostika; rak (medicina)